Association between central obesity and tooth loss in the non‐obese people: Results from the continuous National Health and Nutrition Examination Survey (NHANES) 1999–2012. (10th March 2019) - Kang, Jing; Smith, Scott; Pavitt, Susan; Wu, Jianhua
Abstract: Objectives: This study was to investigate the association between central obesity and tooth loss in non‐obese population. Material and Methods: This national cross‐sectional study included 19436 participants, aged 19–74 years with body mass index(BMI) 18.5–29.9 kg/m 2, from the National Health and Nutrition Examination Survey(NHANES) 1999–2012. Tooth loss was measured by the number of teeth missing. Central obesity was defined by a categorized 3‐level waist circumference according to the WHO recommendation. A zero‐inflated negative binomial model was used to investigate the association between tooth loss and central obesity. All models were adjusted for demographic, socioeconomic status, lifestyles, medical conditions and inflammatory biomarkers. Results: For an overweight person with central obesity, the prevalence of tooth loss increased by 31% (Prevalence ratio [PR]: 1.31, 95% CI: 1.20–1.44) compared with a person with similar BMI but no central obesity, and increased by 40% (PR: 1.40, 95% CI: 1.26–1.56) if compared with a normal‐weight person without central obesity. There was a clear stepwise association between tooth loss and central obesity. Conclusion: The results reveal that central obesity is significantly associated with tooth loss in the non‐obese population, which suggests that non‐obese individuals with central obesity may represent an important target population for oral health preventive strategies.